OPERATING GUIDELINES for the Protection of the Arctic Marine Environment (PAME) Working Group. - Protection of the Arctic Marine Environment (PAME) (Protection of the Arctic Marine Environment (PAME), 2014)
Operating guidelines of the Arctic Council working group Protection of the Arctic Marine Environment (PAME), submitted to the Senior Arctic Officials meeting in Yellowknife, Canada, October 22-23 2014. NOTE: The operating guidelines as presented in this document have not been finally adopted, and should therefore not be viewed as the final version of the operating guidelines.